A study on the required performance of a 2G HTS wire for HTS wind power generators. (17th March 2016) - Sung, Hae-Jin; Park, Minwon; Go, Byeong-Soo; Yu, In-Keun
Abstract: YBCO or REBCO coated conductor (2G) materials are developed for their superior performance at high magnetic field and temperature. Power system applications based on high temperature superconducting (HTS) 2G wire technology are attracting attention, including large-scale wind power generators. In particular, to solve problems associated with the foundations and mechanical structure of offshore wind turbines, due to the large diameter and heavy weight of the generator, an HTS generator is suggested as one of the key technologies. Many researchers have tried to develop feasible large-scale HTS wind power generator technologies. In this paper, a study on the required performance of a 2G HTS wire for large-scale wind power generators is discussed. A 12 MW class large-scale wind turbine and an HTS generator are designed using 2G HTS wire. The total length of the 2G HTS wire for the 12 MW HTS generator is estimated, and the essential prerequisites of the 2G HTS wire based generator are described. The magnetic field distributions of a pole module are illustrated, and the mechanical stress and strain of the pole module are analysed. Finally, a reasonable price for 2G HTS wire for commercialization of the HTS generator is suggested,  reflecting the results of electromagnetic and mechanical analyses of the generator.